2019
DOI: 10.1128/jvi.00530-19
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Depletion Inhibits Bunyavirus Infection via Generation of Noninfectious Interfering Virions

Abstract: Several host and viral processes contribute to forming infectious virions. Polyamines are small host molecules that play diverse roles in viral replication. We previously demonstrated that polyamines are crucial for RNA viruses; however, the mechanisms by which polyamines function remain unknown. Here, we investigated the role of polyamines in the replication of the bunyaviruses Rift Valley fever virus (vaccine strain MP-12) and La Crosse virus (LACV). We found that polyamine depletion did not impact viral RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 43 publications
(32 reference statements)
2
37
1
Order By: Relevance
“…Using the data from infectious titers ( Figure 1 E) and viral genomes ( Figure 1 I), we calculated the specific infectivity (genomes per PFU) and observed that DFMO treatment increased the ratio of genomes to titer ( Figure 1 J), similar to previous findings with bunyaviruses and polyamine depletion. 23 Thus, polyamines enhance coronavirus infection and maintain a specific infectivity of MHV.…”
Section: Resultsmentioning
confidence: 99%
“…Using the data from infectious titers ( Figure 1 E) and viral genomes ( Figure 1 I), we calculated the specific infectivity (genomes per PFU) and observed that DFMO treatment increased the ratio of genomes to titer ( Figure 1 J), similar to previous findings with bunyaviruses and polyamine depletion. 23 Thus, polyamines enhance coronavirus infection and maintain a specific infectivity of MHV.…”
Section: Resultsmentioning
confidence: 99%
“…Because polyamines perform vital roles in viral infections, their depletion disrupts the proliferation of numerous viruses from different families, such as Herpesviridae (HSV-1 and HCMV), Togaviridae (Semliki forest virus, Sindbis virus, and CHIKV), Flaviviridae (dengue virus serotype 1, Japanese encephalitis virus, Yellow fever virus, and ZIKV), Picornaviridae (enterovirus A71, poliovirus, and CVB3), Bunyaviridae (Rift Valley fever virus and La Crosse virus), Rhabdoviridae (rabies virus and Vesicular stomatitis virus) and Coronaviridae (Middle East respiratory syndrome coronavirus [MERS-CoV]) ( Mastrodomenico et al, 2019 ; Mounce et al, 2016a ; Mounce et al, 2016b ; Tuomi et al, 1980 ; Tyms and Williamson, 1982 ). Here, we investigated the impact of polyamines on PRRSV, an Arteriviridae family member.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 was shown to produce comparable amounts of viral particles in cells depleted of polyamines with the specific ODC1 inhibitor DFMO and control cells, but those produced from polyamine-deficient cells had different abundance of DNA fragments [38] and DFMO-treated cells produced lower viral titers [39]. Similarly, the bunyaviruses, Rift Valley Fever virus, and Lacrosse virus produced non-infectious particles in polyamine-depleted cells [40]. Polyamines are present to varying degrees in capsids of diverse viruses.…”
Section: Polyamines In Mammalian Viruses and The Response To Infectionmentioning
confidence: 99%